Rheological properties of emulsions containing modified soy protein isolates - Puppo, María Cecilia (2003)
The feasibility of replacing common emulsifiers with soy protein isolates (SPI) in low-calorie salad dressings was evaluated. Structural modifications of SPI were obtained by thermal-acidic treatment with or without neutralization (TH1.6N and TH1.6, respectively). Modification of flow properties of TH1.6 and TH1.6N emulsions by thermal treatment and different protein concentrations was evaluated through shear stress vs. shear rate measurements in a rotational viscometer. TH1.6N isolates generated emulsions with higher shear stress and apparent viscosity than those prepared with TH1.6. Heated TH1.6N emulsions at 10% protein gave the highest values of shear stress and plastic flow behavior. These emulsions had high consistency, viscosity, and elasticity. TH1.6N isolates had lower emulsifying capacity than TH1.6, probably due to the higher protein aggregation produced during neutralization, which prevented protein unfolding. These isolates would be suitable for the preparation of stable emulsions with adequate consistency and elasticity.